From Self-Reliance to State Recognition: Local Leadership and Social Capital in Transforming an Agrowisata Village into a Climate Village in 2023 - Rambe, Wahyudi; Kenepri, Kenepri; Indah, Aprida; Syamsuadi, Amir; Wahyudi, Prima (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the role of local leadership and social capital in the transformation of RW 05, Agrowisata Village, Pekanbaru City, to formal recognition through the 2023 Main Climate Village Program (ProKlim). Using a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and document studies, then analyzed thematically. The results show that local leadership acts as a catalyst for self-reliance through role models, direct mentoring, and the integration of environmental issues into informal social spaces. Social capital, reflected in the practice of mutual cooperation without incentives, crop exchange, and cross-group trust networks, serves as the foundation for voluntary community participation. Organically formed community institutions, such as the Women's Farmers Group and the reservoir management team, are able to organize activities, document achievements, and provide environmental education. Community-based adaptation practices include the utilization of local resources, simple technological innovations, independent waste management, and intergenerational environmental education. State recognition through ProKlim is bottom-up, born from community initiatives that are then institutionalized, strengthening community legitimacy at the local level. The novelty of this research lies in the integration of five dimensions—local leadership, social capital, institutions, adaptation practices, and state legitimacy—as an analytical framework for understanding the interaction between citizen initiatives and environmental policies. These findings contribute to the development of adaptive, inclusive, and sustainable community-based development models.